The role of traditional risk factors in explaining the social disparities in cardiovascular death: The national health and Nutrition Examination Survey III (NHANES III) - Wei Zhang; Muhammad Imtiaz Ahmad; Elsayed Z. Soliman (Elsevier, 2020)
Objective: ─ To assess the role of traditional risk factors in explaining the association between cumulative social risk exposure and disparities in CVD death among US adults. Methods: ─ The study included 15,906 participants from the Third National Health and Nutrition Examination Survey III who were CVD-free at enrollment. Baseline social risk factors (minority race, poverty-income ratio<1, education<12 grade, and living single) were used to create a cumulative social risk score (0 to ≥3). CVD death served as the primary outcome. We assessed the contribution of each major CVD risk factor to the link between cumulative social risk exposure and CVD death. Results: ─ During a median follow-up of 14 years, 1309 CVD deaths occurred. Participants with elevated cumulative social risk score were at increased risk of CVD death, with hazard ratio 1.19(95%CI 1.01-1.41), 1.52(95%CI 1.28-1.79), and 1.46 (95%CI 1.23-1.74) in individuals with score 1, 2 and ​≥ ​3 respectively, compared with individuals with score of 0. Traditional CVD risk factors explained about one third of the disparities in CVD death in individuals with the elevated social risk exposure. Among the one third effect by combined CVD risk factors, current smoking contributed the largest proportion, accounting for approximately one half of the combined risk factors effect, followed by obesity and diabetes. Conclusions: ─Among the traditional risk factors, control of smoking appears to be the greatest opportunity to attenuate the social disparities in CVD death. While these findings call for further studies to identify other pathways that explain the elevated CVD mortality in socially disadvantaged population.